Quantitative assessment of brain metabolism in mice using non-contrast MRI at 11.7T - Xiuli Yang; Yuguo Li; Hanzhang Lu; Zhiliang Wei (MethodsX)
Brain oxygen metabolism indicates the rate of energy consumption and is a potential marker of pathological changes. Positron emission tomography (PET) is the gold standard for measuring metabolic rates using radioactive tracers. However, its application in preclinical studies, particularly with rodent animals, is constrained by the need for arterial input function measurements and on-site cyclotron facilities for tracer preparation. As an alternative, non-invasive, non-contrast MRI techniques, such as T2-relaxation-under-spin-tagging (TRUST) and phase-contrast (PC) MRI, can be used for evaluating brain metabolism in vivo. This study outlines a step-by-step method for implementing TRUST and PC MRI in mice at 11.7T scanner. The proposed method yields non-invasive, non-contrast quantitative measurements of global brain metabolism in approximately 20 min, paving the way for broader applications in future pathophysiological studies. • Non-invasive and non-contrast assessment of brain metabolism in mice. • Quantitative measurement of metabolic rate in approximately 20 min.